2001
DOI: 10.1590/s0004-282x2001000200006
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evaluation in myotonic dystrophy: correlation with CTG length expansion

Abstract: -In myotonic dystrophy (MD), disease severity has been correlated with expansion of CTG repeats in chromosome 19. The aims of this study were to evaluate efficacy of electromyography in the diagnosis of MD, access the frequency and the characteristics of peripheral involvement in the disease and to verify whether the CTG repeats correlated with the electrophysiological abnormalities. Twenty-five patients and six relatives at risk of carrying the MD gene were examined. Electrical myotonia (EM) was scored. Senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
2
17
1
2
Order By: Relevance
“…Our hypothesis was that the distribution of EM would conform to the distribution of muscle weakness in the two disorders: more distal in DM1 and more proximal in DM2. In DM1, we confirmed that myotonia is far more evocable distally in the arm and leg, as noted by others, 14,21 and all our DM1 patients had distally predominant limb weakness on neurologic examination. Contrary to what we expected, myotonia was also worse distally in DM2, at least in the arm, in which the steepness of the drop-off in myotonia from distal to proximal muscles was not significantly different than in DM1.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our hypothesis was that the distribution of EM would conform to the distribution of muscle weakness in the two disorders: more distal in DM1 and more proximal in DM2. In DM1, we confirmed that myotonia is far more evocable distally in the arm and leg, as noted by others, 14,21 and all our DM1 patients had distally predominant limb weakness on neurologic examination. Contrary to what we expected, myotonia was also worse distally in DM2, at least in the arm, in which the steepness of the drop-off in myotonia from distal to proximal muscles was not significantly different than in DM1.…”
Section: Discussionsupporting
confidence: 91%
“…21 A more recent study of 27 patients confirmed these findings using similar methodology to estimate the severity of myotonia. 14 In 1992, it was reported that the genetic defect underlying classic myotonic dystrophy is an unstable expanded CTG triplet repeat in the untranslated region of the DMPK protein kinase gene on chromosome 19. 3 In the middle to late 1990s, a number of investigators 6,17,18,23,25 reported an autosomaldominant systemic disease very similar to classic myotonic dystrophy, except that the distribution of limbmuscle weakness was often more proximal than distal, muscle atrophy was less, and there was no expansion of the CTG triplet repeat sequence.…”
mentioning
confidence: 99%
“…3,4,12 Some authors have insisted that PN is not uncommon and exists in 20%-30% of patients with DM1. [18][19][20][21] This thesis is supported by electrophysiological, 18,21,22 pathological, 20 and clinical findings. The common feature in these reports is that, in DM1 patients, PN is an axonal neuropathy that tends to progress in a stepwise fashion irrespective of the clinical severity of myopathy.…”
Section: Discussionmentioning
confidence: 79%
“…A linkage to the HMSN genes could not be shown. An association with diabetes mellitus was also largely excluded [4,[6][7][8]. In contrast, in the Index case described in this paper, the reason for polyneuropathy was firmly established by the presence of a CMT1 mutation, in addition to her DM1 mutation.…”
Section: Discussionmentioning
confidence: 77%
“…In the literature there are controversial results for the involvement of the peripheral nervous system in DM. Axonopathy was reported, involving both the motor and the sensory nerves, rather than demyelination in electrophysiological investigation of DM patients [4][5][6][7][8][9]. However, morphological and morphometric analyses of DM1 transgenic mice, carrying 300 CTG repeats, did not reveal axonal degeneration, sensory and motor neuropathy and a significant demyelination [10].…”
Section: Introductionmentioning
confidence: 99%